2010
DOI: 10.1002/chem.200903137
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Controllable Synthesis of Monodisperse CaF2 and CaF2:Ce3+/Tb3+ Hollow Spheres as Efficient Luminescent Materials and Smart Drug Carriers

Abstract: Highly uniform and well-dispersed CaF(2) hollow spheres with tunable particle size (300-930 nm) have been synthesized by a facile hydrothermal process. Their shells are composed of numerous nanocrystals (about 40 nm in diameter). The morphology and size of the CaF(2) products are strongly dependent on experimental parameters such as reaction time, pH value, and organic additives. The size of the CaF(2) hollow spheres can be controlled from 300 to 930 nm by adjusting the pH value. Nitrogen adsorption-desorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(26 citation statements)
references
References 60 publications
0
25
0
1
Order By: Relevance
“…Although template directing is the most straightforward method, this strategy suffers from many disadvantages including high cost and complicated procedures. Thus, one-pot and template-free methods are more attractive and feasible to produce hollow-structured materials [20][21][22][23][24]. Though many efforts have been exerted, it still remains a challenge to obtain hollow structures with uniform morphology and narrow size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Although template directing is the most straightforward method, this strategy suffers from many disadvantages including high cost and complicated procedures. Thus, one-pot and template-free methods are more attractive and feasible to produce hollow-structured materials [20][21][22][23][24]. Though many efforts have been exerted, it still remains a challenge to obtain hollow structures with uniform morphology and narrow size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Pandurangappa et al [9] reported recently the synthesis of CaF 2 nanoparticles by two different techniques namely co-precipitation and hydrothermal, with the grain diameter of 30-35 nm and 20-28 nm, respectively. The literatures of synthesis of CaF 2 nanoparticles or hollow spheres doped with RE ions, such as Yb 3+ [10], Eu 3+ [6,11,12], Tb 3+ [13,14] and Ce 3+ [15], were successively reported. In addition to these RE ions mentioned above, the erbium (Er) element is one important and particular RE ion with rich energy levels, especially the plenty of upconversion emission channels.…”
Section: Introductionmentioning
confidence: 99%
“…As an excellent host material, the lanthanide (III) ions-doped CaF 2 crystals demonstrated unique luminescence properties [17e20]. Our group has reported an easily-made, template-free method for synthesis of hollow mesoporous CaF 2 :Ce 3þ /Tb 3þ microspheres by hydrothermal route [21]. The as-prepared CaF 2 :Ce 3þ /Tb 3þ microspheres showed the strong down-shifting green fluorescence with high quantum yield which is as high as 45% under excitation at 305 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we found that Mn 2þ play an important role of adjusting the upconversion luminescence property and the enhanced MR imaging ability [41e43,54e63]. The UCHNs were prepared according to our previous report with some modification [21]. Typically, a total of 2 mmol of Ca(NO 3 ) 2 $4H 2 O, Mn(NO 3 ) 2 , Yb(NO 3 ) 3 and Er(NO 3 ) 3 (molar ratio Ca: Mn: Yb: Er ¼ 91:5:3:1) and 4 mmol of trisodium citrate (Cit 3À ) were dissolved in deionized water to form 40 mL of solution 1.…”
Section: Introductionmentioning
confidence: 99%